Dynamics and Formation of Obscuring Tori in AGNs - Bannikova, Elena Yu.; Sergeyev, Alexey V. (Frontiers in Astronomy and Space Sciences, 2017)
We considered the evolution of a self-gravitating clumpy torus in the gravitational field of the central mass of an active galactic nucleus (AGN) in the framework of the N-body problem. The initial conditions take into account winds with different opening angles. Results of our N-body simulations show that the clouds moving on orbits with a spread in inclinations and eccentricities form a toroidal region. This mechanism can solve the problem of the geometrical thickness of the torus. The velocity of the clouds at the inner edge of the torus is lower than in a disk model that can explain the observed rotation curves. We discuss the scenario of torus formation related with the beginning of the AGN stage.